Random nanohole arrays and its application to crystalline Si thin foils produced by proton induced exfoliation for solar cells - Lee, Hyeon-Seung; Choi, Jae Myeong; Jung, Beomsic; Kim, Joonkon; Song, Jonghan; Jeong, Doo Seok; Park, Jong-Keuk; Kim, Won Mok; Lee, Doh-Kwon; Lee, Taek Sung; Lee, Wook Seong; Lee, Kyeong-Seok; et al. (NATURE PUBLISHING GROUP, 2019)
We report high efficiency cell processing technologies for the ultra-thin Si solar cells based on crystalline Si thin foils (below a 50 mu m thickness) produced by the proton implant exfoliation (PIE) technique. Shallow textures of submicrometer scale is essential for effective light trapping in crystalline Si thin foil based solar cells. In this study, we report the fabrication process of random Si nanohole arrays of ellipsoids by a facile way using low melting point metal nanoparticles of indium which were vacuum-deposited and dewetted spontaneously at room temperature. Combination of dry and wet etch processes with indium nanoparticles as etch masks enables the fabrication of random Si nanohole arrays of an ellipsoidal shape. The optimized etching processes led to effective light trapping nanostructures comparable to conventional micro-pyramids. We also developed the laser fired contact (LFC) process especially suitable for crystalline Si thin foil based PERC solar cells. The laser processing parameters were optimized to obtain a shallow LFC contact in conjunction with a low contact resistance. Lastly, we applied the random Si nanohole arrays and the LFC process to the crystalline Si thin foils (a 48 mu m thickness) produced by the PIE technique and achieved the best efficiency of 17.1% while the planar PERC solar cell without the Si nanohole arrays exhibit 15.6%. Also, we demonstrate the ultra-thin wafer is bendable to have a 16 mm critical bending radius.
Keywords: LIGHT MANAGEMENT; LAYER-TRANSFER; SILICON; NANOSTRUCTURES; PROGRESS; WAFERS